Exploring Academic Culture in Indonesian Christian Universities Using Hofstede VSM 2013 - Karnawati, Karnawati; Yanto, Heri; Zulaeha, Ida; Mulyono, Sungkowo Edi (Pandawan, 2025)
This study examines the academic culture in Christian universities in Indonesia through the Value Survey Model (VSM) 2013 Hofstede, analyzing its impact on innovation readiness and technopreneurial development. Using a quantitative approach, data were collected through surveys from faculty members and students across several Christian universities. The study employed Structural Equation Modeling (SEM) to analyze the relationships between Hofstede’s cultural dimensions, including power distance, individualism vs collectivism, masculinity vs femininity, uncertainty avoidance, long-term vs short-term orientation, and indulgence vs restraint. Findings indicate that Christian universities in Indonesia exhibit a collectivist academic culture with high uncertainty avoidance and significant power distance, which influence institutional innovation potential. While long-term orientation and masculinity moderately affect academic behavior, constraints in academic freedom and risk-taking hinder the adoption of digital and entrepreneurial initiatives. This study highlights the role of academic culture in shaping innovation readiness and provides strategic recommendations for fostering a more adaptable and competitive academic environment aligned with global technopreneurship trends.